Molecular dynamics simulations of the evolution of residual stresses during rapid solidification of aluminium - Papanikolaou, Michail; Salonitis, Konstantinos; Jolly, Mark R. (Springer, 2021)
It is well known that residual stresses are quite common in castings and they emerge due to uneven cooling conditions. Nowadays, the development of atomistic modelling techniques has allowed for the in-depth investigation of the solidification process mechanics as well as the distribution of residual stresses in the simulation domain. In this study we have performed three-dimensional molecular dynamics simulations to investigate the evolution of residual stresses during homogeneous nucleation in pure aluminium as well as their distribution over the simulation domain. A simulation box containing 1 million aluminium atoms placed on the sites of a face centred cubic (FCC) lattice has been melted and subsequently quenched under various cooling rates. The potential energy as well as the formation of grains has been monitored during quenching stages. Moreover, the present analysis is expanded to the distribution of the grain size and the number of grains as a function of the cooling rate. Finally, the obtained results suggest that the cooling rate significantly affects the distribution as well as the final magnitude of residual stresses in the solidified structure
Keywords: Molecular dynamics; Residual stresses; Cooling rate Aluminium; Grain coarsening Microstructure